A study to assess the unmet need for contraception among married women in the urban field practice area of a medical college - M., Anupama; Iyengar, Krishna; S. S., Rajesh; Jayaram, Ashok; P., Venkatesh (International Journal Of Community Medicine And Public Health, 2019)
Background: The concept of unmet need for family planning points to the gap between some women’s reproductive intentions and their contraceptive behaviour. The National Population policy (NPP) 2000 states that the immediate objective is to address the unmet need for contraceptive services. Unintended pregnancy related to unmet need is a worldwide problem that affects women and their families and societies at large. Methods: A community based cross-sectional study was conducted from November 2016 to October 2017 in Maralur and Maralur Dinne, urban localities under urban health Training Centre of Sri Siddhartha Medical College. 260 Married women (15–49 years) were interviewed by house to house survey. The questionnaire was used to collect data to assess their reproductive intentions and contraceptive behaviour. Results: Out of 260 participants, 144 (55.4%) of them belonged to the group where their contraceptive needs were met for spacing and limiting births, 59 (22.69%) of them of did not have any need for contraceptives, 16 (6.15%) had unmet need for spacing births and 41 (15.77%) of the participants had unmet need for limiting births. Conclusions: The unmet need for contraceptives was 21.92% in the study which is much higher compared to NFHS-4 data for urban India (12.1%). The reasons and the factors associated with the unmet need should be addressed.